Juninas Quadrilhas: cultural or media heritage? (Revista Internacional de Folkcomunicação, 2018)
ABSTRACT The present article aims to understand the relationship between the media and the cultural heritage that is established from the Juninas Quadrilhas in the Brazilian Northeast. Specifically, we intend to conceptualize the cultural patrimony that presents a dichotomy: material and immaterial and indicate the communication changes in the Juninas Quadrilhas from the historical process trodden by the Juninas Quadrilhas that were considered spontaneous or folklorized and that are being converted into Institutional and manipulated Grips by media interests. The methodological cut will be at the Globo Juninas Quadrilha Festival, in 2017, at SESC-Goiânia in Pernambuco. In the initial results, it is intended to legitimize the Juninas Quadrilhas as intangible cultural heritage. KEY-WORDS Media; Communication; Cultural heritage; Junina Quadrilha.